(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Tapwal A, Kumar R, Pandey S. 2013. Diversity and frequency of macrofungi associated with wet ever green tropical forest in Assam, India. Biodiversitas 14: 73-78. A study was conducted in Jeypore Reserve Forest located in Assam, India to investigate the diversity of macrofungi associated with different tree species. The diversity of broad leaves trees and high humidity during monsoon period favours ideal growth of diverse group of macrofungal fruiting bodies. Thirty macrofungal species representing 26 genera belonging to 17 families were collected from six different sites in the study area. Out of these maximum six genera assignable to family Polyporaceae, five genera to Russulaceae, three genera to Agaricaceae, two genera to Ganodermataceae and Cantharellaceae each and rest of the families were represented by single genus only. The ecological preference of the species reveled that maximum (17) species were saprophyte, living on dead substrates or decaying wood debris, ten species were found associated with roots of higher trees, while three species were found parasitic. Overall 20 species were found edible including some species having medicinal utilization. The present study revealed that maximum frequency of occurrence was exhibited by Trametes versicolor and Schizophyllum commune (83.33%), followed by Microporus xanthopus, Pycnoporus sanguineus (66.67%) and Coprinus disseminates (50%). The rest of the species exhibited the frequency distribution ranging between 16.67-33.33%. The maximum density was recorded for Schizophyllum commune (126.67%) followed by Trametes versicolor (120%) and Xylaria polymorpha (93.33%). The density of rest of the species were ranged between 3.33- 6.67%. The key objective of the present study was to generate a database on macrofungal diversity of Jeypore Reserve Forest along with their ecological preferences and utilization, which is not earlier documented.